What is Africa's problem? - Museveni, Yoweri, 1944- (University of Minnesota Press, 2000)
Edited by Elizabeth Kanyogonya"I am very pleased that this book by one of Africas most important leaders now will be available to Americans. We need to understand what Africans think about Africa."Jimmy Carterand/orWhat is Africas problem? As one of the leaders expressing a broad and forceful vision for Africas future, Ugandas Yoweri K. Museveni is perhaps better placed than anyone in the world to address the very question his book poses.